Literary Criticism of Milenko Maticki - Đuričković, Milutin B. (Collection of Papers of the Faculty of Philosophy in Priština, 2023)
The main purpose of this paper is to enlighten literary critical thought and work of Milenko Maticki (1936-2001), a well-known writer for young people, as well as for adults. In the constant touch with literature, and in the capacity of editor of Politics for Children, Maticki based his literary-critical contributions on strict selection and valid aesthetic-artistic criteria, showing his poetic affinities and good knowledge of literary theoretical and methodological parameters, which confirmed his creative agility and presence on the ex-Yugoslav literary scene. The paper shows that the literary criticism of Milenko Maticki, despite its professional quality and undoubted value, stayed in the shadow of his prose for young readers.